Comprehensive Characterization of Cachexia-Inducing Factors in Diffuse Large B-Cell Lymphoma Reveals a Molecular Subtype and a Prognosis-Related Signature - Kuang, Zhixing; Li, Xun; Liu, Rongqiang; Chen, Shaoxing; Tu, Jiannan (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background:  Cachexia is defined as an involuntary decrease in body weight, which can increase the risk of death in cancer patients and reduce the quality of life. Cachexia-inducing factors (CIFs) have been reported in colorectal cancer and pancreatic adenocarcinoma, but their value in diffuse large B-cell lymphoma (DLBCL) requires further genetic research. Methods: We used gene expression data from Gene Expression Omnibus (GEO) to evaluate the expression landscape of 25 known CIFs in DLBCL patients, and compared them with normal lymphoma tissues from two cohorts (GSE56315 [n=88] and GSE12195 [n=136]). The mutational status of CIFs were also evaluated in The Cancer Genome Atlas (TCGA) database. Based on the expression profiles of 25 CIFs, a single exploratory dataset which was merged by the datasets of GSE10846 (n=420) and GSE31312 (n=498) were divided into two molecular subtypes by using the method of consensus clustering. Immune microenvironment between different subtypes were assessed via single-sample gene set enrichment analysis (ssGSEA) and the CIBERSORT algorithm. The treatment response of commonly used chemotherapeutic drugs was predicted and Gene-set Variation Analysis (GSVA) was utilized to reveal the divergence in activated pathways for distinct subtypes. A risk signature was derived by univariate Cox regression and LASSO regression in the merged dataset (n=882), and two independent cohorts (GSE87371 [n=221] and GSE32918 [n=244]) were used for validation, respectively. Results: Clustering analysis with CIFs further divided the cases into two molecular subtypes (cluster A and cluster B) associated with distinct prognosis, immunological landscape, chemosensitivity, and biological process. A risk prognostic signature based on CCL2, CSF2, IL15, IL17A, IL4, TGFA, and TNFSF10 for DLBCL was developed, and significant differences in overall survival analysis were found between the low-risk and high-risk groups in the training dataset and another two independent validation datasets. Multivariate regression showed that the risk signature was an independently prognostic factor in contrast to other clinical characteristics. Conclusions: This study demonstrated that CIFs further contribute to the observed heterogeneity of DLBCL, and molecular classification and a risk signature based on CIFs are both promising tools for prognostic stratification, which may provide important clues for precision medicine and tumor-targeted therapy.